PERANCANGAN BUKU CERITA ILUSTRASI EDUKASI DAN KOMUNIKATIF “LEGENDA GUNUNG TAMPOMAS” UNTUK ANAKUSIA 7-9 TAHUN: Designing of Educational and Communicative Illustrated Storybooks “The Legend of Mount Tampomas” for Children 7-9 Years Old - Prasetyo, Martinus Eko; Angelia Caroline (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2024)
Designing of Educational and Communicative Illustrated Storybooks “The Legend of Mount Tampomas” for Children 7-9 Years Old. This study aims to create an informational medium about the folklore or legend of Mount Tampomas for children aged 7-9 years in the form of an illustrated book. This folklore is a legend derived from the regional story of Sumedang district. The effort will be to package this folklore into an attractive, educational, and communicative illustrated story to capture the interest of children aged 7-9 years, helping them better understand the history of folklore. The design of the illustrated folklore book includes visual illustrations and minimal text tailored to the children's world. This study was conducted using a qualitative descriptive research method, utilizing techniques such as distributing questionnaires to respondents and reading information from literature studies. The final goal of this illustrated folklore book design research is to create an educational and communicative illustrated folklore book. It is expected to become a medium to introduce the folklore of the Legend of Mount Tampomas to children.